Highly similar morphologies between chromosomes bearing U2 snRNA gene clusters in the group Astyanax Baird and Girard, 1854 (Characiformes, Characidae): An evolutionary approach in species with 2n = 36, 46, 48, and 50 - Piscor, Diovani [UNESP]; Centofante, Liano; Parise-Maltempi, Patricia Pasquali [UNESP] (SAGE Publications, 2016)
Repetitive sequences and their chromosomal locations have been widely studied in species of the Astyanax genus. However, the chromosomal organization of U2 snDNA remains largely unknown. The aims of this study were to examine the chromosomal contexts of U2 snRNA and 5S rRNA genes in Astyanax species and determine the degree of chromosome morphological similarity between species with different diploid numbers. Clusters of U2 snDNA and 5S rDNA were determined in nine species of Astyanax, including two karyomorphs of Astyanax fasciatus Cuvier, 1819. All species exhibited U2 snDNA clusters on two chromosome pairs, except Astyanax mexicanus De Filippi, 1853 (one pair). The 5S rDNA clusters were located on one chromosome pair in Astyanax altiparanae Garutti and Britski, 2000, and Astyanax marionae Eigenmann, 1911, two pairs in Astyanax abramis Jenyns, 1842, Astyanax asuncionensis Géry, 1972, Astyanax bockmanni Vari and Castro, 2007, Astyanax eigenmanniorum Cope, 1894, A. fasciatus (karyomorphs I and II), and Astyanax schubarti Britski, 1964, and four pairs in A. mexicanus. The relationships between the repetitive sequences in different species suggest that A. schubarti and A. mexicanus exhibit an unusual U2 snDNA chromosomal format as a result of events occurring in the evolutionary history of the Astyanax group.
Keywords: 5S rDNA; FISH; karyotype evolution; Mexican blind cavefish; repetitive DNA